Modelling tropospheric radio-attenuation parameters for tropical countries. The Venezuela case - Muñoz íngel; Pacheco, Ronald; Cubillán, Nestor; Durante Rincón, Carlos Alberto; Durán, Larissa; Fermín, José (Ciencia)
Several tropospheric radio-attenuation parameters for the 0.4-4.0 GHz window are modeled in the present work. Both the Hopfield and Linear models were used to obtain vertical profiles of Venezuelan tropospheric refractivity. The extinction coefficient spectra is determined via Kramers-Kr í¶nig relations. Rain attenuation contours and their monthly time evolution are presented for different Venezuelan locations.